Diffuse parenchymal lung disease. (June 2016) - Fiddler, Christine; Parfrey, Helen
Abstract: Diffuse parenchymal lung diseases are a heterogeneous group of disorders characterized by inflammation and fibrosis of the pulmonary interstitium. They are collectively referred to as interstitial lung diseases (ILD), although this term is a misnomer as it includes disorders that also affect the alveolar space. Many of these entities are of unknown cause and little is understood about their pathogenesis. However, the classification, prognosis and treatment of ILDs continue to evolve as our understanding of the disease process improves. This presents a considerable challenge to the clinician in establishing not only a confident diagnosis, but also a patient-centred, personalized treatment plan to achieve remission or disease stabilization. This article provides an overview of how to evaluate a patient with suspected ILDs, including a diagnostic algorithm. Current management strategies for the more commonly encountered ILDs including idiopathic pulmonary fibrosis, sarcoidosis, connective tissue disease-associated ILD and hypersensitivity pneumonitis, are discussed.